Faktor-Faktor yang Berhubungan dengan Penerimaan Vaksinasi HPV (Human Papilloma Virus) pada Siswi SD Negeri 54 Kendari Tahun 2024 - Dewi Ceriani Maha; Hariati Lestari; Akifah Akifah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2026)
Health is one aspect of human life that can improve the quality of life and productivity of the workforce. The high morbidity and mortality rates in society cause reduced physical work ability, cancer is one of the leading causes of death worldwide. Cervical cancer is a form of malignancy that occurs in the cervix in women, this disease is related to infections caused by the Human Papilloma Virus (HPV). The most appropriate age to vaccinate is 9-14 years or before women have sexual intercourse. The method in this study is a quantitative analytical method with a cross-sectional approach. The population in this study were 58 female students in grades 5 and 6 of SD Negeri 54, Kendari City. The sampling technique in this study was total sampling, namely a sampling technique where the number of samples is the same as the population. The findings of this investigation indicate a relationship between family support (0.009) and side effects (0.010) with HPV vaccine acceptance, and there is no relationship between parental knowledge (0.169) with HPV vaccine acceptance in female students of SD Negeri 54 Kendari in 2024. Parents need to be more active in seeking correct information from trusted sources, and can provide full support to their children to complete the vaccine dose according to schedule. For this reason, it is very important for children to get the complete HPV vaccine.